Complement activation in atypical hemolytic uremic syndrome and scleroderma renal crisis: a critical analysis of pathophysiology - Zuckerman,Roman (2018)
ABSTRACT Scleroderma is an autoimmune disease that affects multiple systems. While pathophysiologic mechanisms governing the development of scleroderma are relatively poorly understood, advances in our understanding of the complement system are clarifying the role of complement pathways in the development of atypical hemolytic uremic syndrome and scleroderma renal crisis. The abundant similarities in their presentation as well as the clinical course are raising the possibility of a common underlying pathogenesis. Recent reports are emphasizing that complement pathways appear to be the unifying link. This article reviews the role of complement system in the development of atypical hemolytic uremic syndrome and scleroderma renal crisis, and calls for heightened awareness to the development of thrombotic angiopathy in patients with scleroderma.